Reaching the millions: accelerating agricultural extension services through Information and Communication Technologies (ICTS) - Ali, Muhammad; Man, Norsida (International Digital Organization for Scientific Information, 2017)
Agricultural extension is considered to be the main vehicle in transporting the valuable pieces of advises to the farming community. However, the pace of delivery can be increased by incorporating Information and Communication Technologies (ICTs). Extending and receiving desired information within less fraction of time has become priority and need of the hour particularly in this era of agricultural intensification. In fact, common farmers now want quick advisory services with less mobility. So, ICTs can be the appropriate solution in order to speed up the process of agricultural technology transfer. Moreover, extension services can be improved with the proper use of ICTs and help in poverty alleviation, combating food insecurity issue and exchange of agriculture innovations, reaching majority of the farmers at regional and global level. Relevant review of literature was adopted as desk research for this study. The crux of the reviewed literature revealed that the new nexus between extension and ICTs will lead to impact oriented extension and advisory services and feeding the million mouths.